Macedoński fenomen wzrostu liczby tłumaczeń z języka polskiego w latach 1990-2020 - Tanuševska, Lidija; Łukomska, Natalia (Przekłady Literatur Słowiańskich, 2022)
This article presents the rise of translated Polish literature to the Macedonian language in the thirty years period since Macedonia gained independence from Yugoslavia and transformed from a socialist to a capitalist system. The rise of private publishing houses automatically meant the rise of translating from other languages; in addition, the rise of foreign funds and especially the financial support by the EU in culture was a relevant factor for developing literary translations from Polish to the Macedonian language. The main part of this article is about the works which have been translated, their importance and the methods used in making the choices on what to translate.